Investigation of the Positional Relationship Between the Tympanic Segment of the Chorda Tympani and the Incus in Patients With Otosclerosis or Middle Ear Anomalies Using Ultra-High Resolution Computed Tomography - Aya Katsura; Shinsuke Kaneshiro; Harukazu Hiraumi; Makiko Obara; Akio Tamura; Kiyoto Shiga; Kunihiro Yoshioka (Radiology Research and Practice, 2025)
Conclusion: U-HRCT is useful for detecting the relationship between the chorda tympani and the long crus of the incus in patients with otosclerosis or middle ear anomalies.